2000
DOI: 10.1007/s004640000169
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for stage III colon cancer

Abstract: Based on this study, laparoscopic colectomy in patients with stage III colorectal cancer is oncologically adequate. It results in a long-term outcome comparable to that of traditional open surgery and is associated with low perioperative mortality and morbidity (lower wound infection rate, lower wound recurrences at trocar sites) and a shortened length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 28 publications
7
62
0
6
Order By: Relevance
“…In addition to the growing international experience with singleport laparoscopic colorectal resection, laparoscopic colorectal resection using transrectal assistance, where tra nsrectal access is used for specimen extraction [26] , insertion of the anvil of a circular stapler for intracorporeal double stapled anastomosis [27,28] , or both [29] has been described. Transvaginal access has also been used as an extraction site following colorectal resection [30] as well part of a hybrid NOTES laparoscopic rectosigmoid dissection [31] where significant portions of the dissection are performed transvaginally.…”
Section: Transcolonic/transanal Notes: Human Experiencementioning
confidence: 99%
“…In addition to the growing international experience with singleport laparoscopic colorectal resection, laparoscopic colorectal resection using transrectal assistance, where tra nsrectal access is used for specimen extraction [26] , insertion of the anvil of a circular stapler for intracorporeal double stapled anastomosis [27,28] , or both [29] has been described. Transvaginal access has also been used as an extraction site following colorectal resection [30] as well part of a hybrid NOTES laparoscopic rectosigmoid dissection [31] where significant portions of the dissection are performed transvaginally.…”
Section: Transcolonic/transanal Notes: Human Experiencementioning
confidence: 99%
“…A la luz de las ultimas publicaciones 11,15 , sería lícito efectuar resecciones en pacientes con afectación serosa del tumor, a condición de que el cirujano sea experimentado, con una cuidadosa técnica quirúrgica y controle minuciosamente sus resultados.…”
Section: Indicaciones Del Abordaje Laparoscópico En El Cáncer De Colonunclassified
“…1 Laparoscopic surgery for colon and rectal diseases has been performed increasingly in many institutions with the advances in techniques and instruments, and many studies have reported the usefulness of laparoscopic surgery for colorectal malignancy. [2][3][4][5][6][7] Lacy et al reported that laparoscopic colectomy is superior to open surgery in terms of cancer-related survival. 8 However, cases with rectal cancer were excluded in their study.…”
Section: Introductionmentioning
confidence: 99%